The Relationship Between Internet Use Patterns, Nomophobia, and Fomo With The Incidence of Mental Disorders in Adolescents and College Students : A Scoping Review - Muhammad Farhant Ruksanan; Suryani Suryani; Imas Rafiyah; Ruksanan Ruksanan (Jurnal Ners, 2026)
Abstract The rapid growth of digital technology has significantly reshaped adolescents' lifestyles and mental well-being. Excessive internet use, coupled with nomophobia and Fear of Missing Out (FoMO), has been linked to higher psychological distress among teenagers. This scoping review aims to map the relationship between internet use patterns, nomophobia, and FoMO with mental health outcomes in adolescents. Literature searches were conducted through PubMed, ScienceDirect, EBSCO Medline, and Google Scholar using the Joanna Briggs Institute (JBI) PCC framework and PRISMA guidelines for the period 2015–2025. Ten eligible studies were analyzed. Findings indicate that FoMO consistently predicts nomophobia and digital anxiety. Intensive and entertainment-oriented internet use increases stress and depression risk, while academic-oriented use has a protective effect. Nomophobia emerges as a multidimensional phenomenon influenced by emotional, behavioral, and contextual factors. It is concluded that FoMO and nomophobia are significant contributors to adolescent mental disorders. Nursing interventions should focus on digital self-regulation, FoMO reduction, and digital literacy education to promote psychological well-being among adolescents. Keywords : Internet Use, Nomophobia, Fear Of Missing Out, FoMO, Mental Health, Adolescents